2021
DOI: 10.1002/ece3.7459
|View full text |Cite
|
Sign up to set email alerts
|

The effects of four decades of climate change on the breeding ecology of an avian sentinel species across a 1,500‐km latitudinal gradient are stronger at high latitudes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(148 reference statements)
0
2
0
Order By: Relevance
“…They also reported that the median first egg date correlated significantly with increasing mean May to July temperatures. Vega et al (2021) similarly described an advancement of 8.3 days in start of breeding, as measured by hatching time, in the northernmost populations of European Pied Flycatchers compared to 3.6 days advancement in the southernmost flycatchers over a 36‐year span. As in the previous study, increasing temperature as well as vegetation greenness were important factors in advancing breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the median first egg date correlated significantly with increasing mean May to July temperatures. Vega et al (2021) similarly described an advancement of 8.3 days in start of breeding, as measured by hatching time, in the northernmost populations of European Pied Flycatchers compared to 3.6 days advancement in the southernmost flycatchers over a 36‐year span. As in the previous study, increasing temperature as well as vegetation greenness were important factors in advancing breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…In diurnal migrants, longer photoperiods allow for longer duration of activity while migrating (Alerstam, 2009;Pokrovsky et al, 2021), which is predicted to lead to greater foraging ability during migration and fewer stopovers (or migration slowdowns) in a fly-and-forage migration strategy (Berthold et al, 2001;Alerstam, 2003;Alerstam, 2009). Numerous studies have examined migration timing at a specific point during migration, such as at arrival, departure, or specific stopovers (McKellar et al, 2013;Van Doren and Horton, 2018;Schmaljohann, 2019;Conklin et al, 2021;Lomas Vega et al, 2021;Tomotani et al, 2021). However, few studies have examined the entire migration process (Schmaljohann and Both, 2017;McKinnon and Love, 2018) and studies examining the interaction between timing, rate, and en route conditions in birds are also exceptionally rare (Haest et al, 2020).…”
Section: Introductionmentioning
confidence: 99%